Hubungan antara Karakteristik, Pengetahuan dengan Kejadian Kanker Serviks - Magdalena Eijer Gee; Adelina Lebuan; Justina Purwarini (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2021)
This study aims to determine the relationship between characteristics, knowledge, and the incidence of cervical cancer in the hospital. The research design was correlative descriptive with the cross-sectional approach. The results showed that there was no relationship between age and the incidence of service cancer in the hospital with a p-value of 0.099 (p> 0.05), on the education variable (p-value = 0.003), occupation (p-value = 0.030), parity. (p-value = 0.013), knowledge (p-value = 0.007). In conclusion, there is a significant relationship between education, occupation, parity, and knowledge of respondents with the incidence of cervical cancer in the hospital. Keywords: Reproductive Health, Knowledge, Health Promotion